Relationship between hip muscle strength and lower extremity injuries in soccer players - Ulloa, A. Y.; Miranda, E. A.; Parra, C. P.; Saldivia, F. B.; Gomis, M. J. G.; Silva, N. B. F.; Díaz, G. C. (Scientific Journal of Sport and Performance, 2022)
The objective of this review was to analyse the relationship between hip strength and lower extremity injuries in soccer players. PubMed, Scopus and WOS databases were reviewed. The initial search yielded a total of 613 studies, of which 6 were selected. The studies evaluated the movements of hip adduction, abduction, flexion and extension, in different positions, through dynamometry, concluding that the decrease in hip strength is a risk factor for lower extremity injuries in youth and professional soccer players, which can be determined through isometric, concentric, and eccentric strength testing.